The influence of the paraffin content on the effect exerted by the weighting component on the effect of the depressant additive; Химия и химическая технология в XXI веке; Т. 2 - Efanova A. O. (Химия и химическая технология на иностранном языке (английский), 2023)
Заглавие с титульного экрана